Policies and performance of Ethiopian cereal markets - Rashid, Shahidur; Negassa, Asfaw (University of Pennsylvania Press, 2012)
Cereal is the single largest subsector of Ethiopia’s agriculture. It dominates in terms of its share in rural employment, agricultural land use, and calorie intake, as well as its contribution to national income. The subsector accounts for roughly 60 percent of rural employment, about 73 percent of total cultivated land, more than 40 percent of a typical household’s food expenditure, and more than 60 percent of total calorie intake. The contribution of cereals to the national income is also large. According to available estimates, cereals’ contribution to agricultural value-added is 65 percent, which translates to about 30 percent of gross domestic product (GDP).